Application of radio frequency pasteurization to corn (Zea mays L.): Heating uniformity improvement and quality stability evaluation. (July 2016) - Zheng, Ajuan; Zhang, Bo; Zhou, Liyang; Wang, Shaojin
Abstract: Mildews caused grain losses and serious outbreaks have been becoming increasing concerns in domestic and international corn processing industry. This study intended to explore the possibility of using radio frequency (RF) heating as an effective treatment to eliminate the mold contamination and reduce the damage to corn quality. A pilot-scale, 27 MHz, 6 kW RF unit was used to study the heating uniformity in corn samples with five moisture contents (MC) and using three plastic material containers, and develop a treatment protocol for a corn sample with the MC of 15.0% w.b. and evaluate quality attributes and storage stability of treated samples. The results showed that only 7.5 min was needed to raise the central temperature of 3.0 kg corn samples from 25 °C to 70 °C using the RF energy, but 749 min for samples to reach 68.6 °C using hot air at 70 °C. The RF heating uniformity was improved by adding forced hot air, moving samples on the conveyor, and mixing during the treatment. An effective RF treatment protocol was finally developed to combine 0.8 kW RF power with a forced hot air at 70 °C, conveyor movement at 6.6 m/h, two mixings, and holding at 70 °C hot air for 14 min, followed by forced room air cooling through thin-layer (2 cm) samples. Corn quality was not affected by RF treatments since quality parameters of RF treated samples were better than or similar to those of untreated controls after the accelerated shelf life test. RF treatments may hold great potential as a pasteurization method to control molds in corns without causing a substantial loss of product quality. Highlights: RF heating uniformity was improved by hot air surface heating, moving, mixing and holding. RF treatment protocol was developed for achieving the required pasteurization in corns. Corn quality was maintained after RF treatment and storage. This provided potential RF pasteurization methods for industrial applications.